Correlation of pontic design and partial edentulous areas: A one year cross sectional study - Nikzad S.; Azari A.; khosravi M.; Nezadi A. (Tehran University of Medical Sciences, 2008)
"nBackground and Aim: By definition, pontic is an artificial replacement of missing tooth (teeth) which is essentially used to establish function and esthetics. In order to this fact that, pontic(s) is not completely the same as tooth (teeth) to be replaced, it may not be concern as a simple type of restoration to achieve the best result, it must be design from the esthetically and hygienically point of view as well as comfort, demand and tissue health of patient. The main purpose of this study is to investigate the pontic designs and their relationship to edentulous partial aras. "nMaterials and Methods: 73 pontics in 57 patients have been included in this cross-sectional study. These patients were under treatment in the department of prosthodontics. A primary cast was achieved from each patient and then the cross-sectional contour of edentulous ridge was depicted. For each patient the type of pontic design was derived from textbook standards and then compared with the design of actual verified Prosthesis at delivery. The shape of tissue surface of each denture was determined by a low viscous impression material. The result of each comparison was recorded in a chart data set. "nResults: The most common pontic design was Modified ridge lap with frequency of 93.2%. The type of ridge was %45.2 normal, %19.2 class I, %8.2 class II and %27.4 class III, respectively. %72.6 of pontics tested have inappropriate design in tissue surface. "nConclusion: It seems that in a high percentage of cases the tissue surface contour of prescribed pontics in department of prosthodontics was incorrect and more attention must be paid to the education of students and technicians.